Adaptive Viterbi algorithm with ARQ for bounded complexity decoding. - Harvey, B.A (IEEE Transactions on wireless communications)
Adaptive bounded computational and memory requirements for a Viterbi decoder can be achieved using an error trapping Viterbi decoder algorithm initially develop for hybrid automatic repeat request (ARQ) implementations. Partial path metrics and a sliding window are used to eliminate unreliable paths in the decoder trellis thus reducing the computational and memory requirements. An ARQ is issued if all paths are eliminated. The algorithm is adaptive allowing the receiver to dynamically allocate memory and processing, to improve reliability or received packets, or to reject packets with lower reliability to avoid buffer overruns. The result is the ability to trade off resources versus delay and throughput.